Análisis discursivo de los contenidos que generó el medio digital “FIERRO URCO NO SE TOCA” en las plataformas digitales facebook e instagram”, periodo noviembre 2021 – marzo 2022. - Brito Zuñiga, Nuve Esperanza (2022)
This work analyzes the discourse of the platform "Fierro Urco No Se Toca" in social networks such as Facebook and Instagram. The proposed research methodology is mixed or qualitative-quantitative, the objective is to collect quantitative data by means of the survey, and qualitative data by means of the files and interviews, making it possible to know from the calculations and interpretation of data collected from the analyzed environment. The results show that the message of struggle for the defense of the Fierro Urco moor ecosystem has been strengthened, which is why many have joined the platform on their social networks. In addition, the results show the presence of journalistic genres such as: infographics, video, photography, illustration, photomontage, both on Facebook and Instagram. The information in terms of the function of the message is informative and appealing in most of the analyzed publications. On the other hand, it is observed that in few publications the function is aesthetic or linguistic. As far as sources are concerned, use is limited. In the conclusions of the survey and interviews, it was determined that image and text are of vital importance for a dynamic reception of the message by its followers. Another key element is digitalization, since it allows residents to express themselves, in case the media does not allow the citizen's voice to be heard. In order to determine the environmental discourse, the data collection forms were ideal, where mainly the identifying words were found, such as: stand up for human and nature rights, water is given to you by mother nature, and hashtags such as: #desprivatizarElAgua, #ÚnetePorElPlaneta, #DerechosDeLaNaturaleza, #ProtejamosFierroUrco, which denotes the intention of the "Fierro Urco No Se Toca" platform to disseminate information for the protection of the environment. KEY WORDS: environmental discourse, journalistic genres, language, social networks, semiotics.